Development of ready to cook vegetable khichadi mix by microwave drying technology - Khandekar, S P; Ranveer, R C; Sahoo, A K (Journal of Postharvest Technology, 2020)
This study was undertaken with the objectives of to develop ready to cook Vegetable Khichadi Mix and to optimize its procedure by using microwave drying technique. Instant Vegetable Khichadi is formulated with use of parboiled rice, red gram dhal, green gram dhal and vegetables (Cauliflower, French beans, green peas and carrot). Raw ingredients were converted into instant by soaking and cooking followed by microwave drying (100 W). Instant Khichadi mix was formulated by using various combinations of selected samples of dehydrated rice, dhals and vegetables. The best combination of Instant Khichadi was selected based on sensory analysis (9 point hedonic). Per serving size (100gm) of the Instant Khichadi included 60g rice, 20g dhal and 20g vegetables and required 5 min to cook. Under ICDS, Instant Khichadi Mix can be suggested as a means of supplementary nutrition to incorporate healthy, nutritious food.